DEFORMATIONS AND THE SEQUENCE OF THE STRUCTURES FORMATION IN THE NORTHERN PART OF THE ZONE OF DEVELOPMENT OF MAKSUTOVO METAMORPHIC COMPLEX (SOUTHERN URALS) - B. G. Golionko; A. V. Ryazantsev (Известия высших учебных заведений: Геология и разведка, 2018)
Composition and structural evolution of the Maksutovo metamorphic complex in the its northern part has been examined. The early folds 77) plunging in the SE direction have been established to be developed only in the rocks of the Maksutovo metamorphic complex. The problem of the definition of the geodynamic nature of the 7Л deformation stage, marked by the folds 77), has not been solved yet. Tectonic inclusions of the metamorphic rocks adjacent to the western border of the Main Uralian Thrust without traces of 7Л deformation stage must not be considered as parts of the Maksutovo metamorphic complex. 7Л1 deformation stage expressed in formation of thrusts and 77. west vergent folds is connected with late Paleozoic continental collision. The third stage of deformation 7JIII is marked by development of 77) folds with steep hinges associated with post collision strike slip movements